Peran Pendidikan Agama Islam dalam Memperkuat Moderasi Beragama - Azka N. Achmad; Aditya Aprodicto; Brivan A. Studynka; Maulana Rafli; Rio Raissa; M. Hisyam Al Ghifari (Jurnal Budi Pekerti Agama Islam, 2024)
Islamic religious education has been widely developed at every stage of school, where the aim of this education is to introduce religion as a way of life to teenagers or children at an age before puberty. Islamic religious education also has an impact on strengthening religious moderation. What is meant by religious moderation is an effort to understand the followers of the Islamic religion so that they practice its teachings without being trapped in two extreme poles, namely too loose or too strict. To provide this understanding not only through preaching at religious studies, it can be done in the world of education which has great potential in providing an understanding of the Islamic religion for its adherents. School education itself has a theory for understanding and its objects are very clear to children or teenagers, so it has the potential to strengthen religious moderation.